Cytokine tatus in patients with recurrent herpes infection - A. S. Akmeeva; R. B. Zhamborova; A. Ya. Aloeva; A. M. Kakhidov; I. D. Abdulkadyrova; D. M. Altamirova; Z. A. Kambachokova; T. Sh. Tagirova; A. E. Elkham (Антибиотики и Химиотерапия)
The study of the concentration of the main pro-inﬂammatory cytokines (IL-1β, IL-6 and TNF) in the blood serum of 48 patients with recurrent chronic herpesvirus infection was carried out. A signiﬁcant increase of cytokine levels with the maximum values during the height of the disease was established. During the period of clinical symptoms’ subsidence, a decrease in their concentration with incomplete normalization is observed during the period of convalescence. Changes in the level of IL-1β, IL-6 and TNF in the blood serum of patients with recurrent herpesvirus infection depended on the period of the disease and the severity of the pathological process.